2009
DOI: 10.1021/ic900654m
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of the First Discrete 3d−4f−4f Triple-Stranded Helicate

Abstract: The connection of an additional bidentate chelating unit at the extremity of a segmental bis-tridentate ligand in L5 provides an unprecedented sequence of binding sites for the self-assembly of heterometallic 3d-4f triple-stranded helicates. Thorough thermodynamic and structural investigations in acetonitrile show the formation of intricate mixtures of complexes when a single type of metal (3d or 4f) is reacted with L5. However, the situation is greatly simplified when Zn(II) (3d-block) and Lu(III) (4f-block) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…the condition u L;L triÀ;triÀ ¼ u L;L biÀ;biÀ ¼ u L;L biÀ;triÀ ¼ u L;L complies). Granting the two standard assumptions pertinent to helicate assemblies based on semi-rigid ligands that i) no hairpin or strained structures are formed and ii) the principle of maximum siteoccupancy prevails, [9c,d] application of Equation (10) to, for example, the Equilibrium (11) leading to the recently reported bimetallic trinuclear complex HHH-A C H T U N G T R E N N U N G [Lu 2 Zn(L1) 3 ] 8 + [24] gives the corresponding Equation (12…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…the condition u L;L triÀ;triÀ ¼ u L;L biÀ;biÀ ¼ u L;L biÀ;triÀ ¼ u L;L complies). Granting the two standard assumptions pertinent to helicate assemblies based on semi-rigid ligands that i) no hairpin or strained structures are formed and ii) the principle of maximum siteoccupancy prevails, [9c,d] application of Equation (10) to, for example, the Equilibrium (11) leading to the recently reported bimetallic trinuclear complex HHH-A C H T U N G T R E N N U N G [Lu 2 Zn(L1) 3 ] 8 + [24] gives the corresponding Equation (12…”
Section: Resultsmentioning
confidence: 99%
“…As is often the case for this type of system, a number of other (homometallic) species were also identified as key intermediates in the self-assembly of HHH-A C H T U N G T R E N N U N G [Lu 2 Zn(L1) 3 ] 8 + . [24] Within the precincts of the criteria discussed above, similar treatment for these Equilibria (15), (17) and (19) thus gives a corresponding set of Equations (16), (18) and (20) ( Figure 2). Note that apart from the stoichiometries inferred from ESI-MS and UV/Vis titrations, very little structural information is available for the intermediate species [24] and their cumulative macroscopic stability constants are modelled by the sum of the microscopic formation constants characterising the different conceivable structural isomers (or microspecies) present at equilibrium ( Figure 2 and Appendix I in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 One such example of higher orders of self-assembly has been demonstrated by Ward et al 6 In this work they demonstrate the formation of triple helix comprised of three infinite chains of double helicates. The basic unit is a bis-bidentate ligand which forms a dinuclear double helicate with Ag(I) (e.g.…”
Section: -24mentioning
confidence: 68%
“…For instance, N ‐oxide binaphthol derived ligands wrap around three independent Na + or Li + ions to form trinuclear triple‐stranded helicates 7a. Additionally, recent studies demonstrated that transition‐metal ions [Co(II/III),8a,8c,8d Ga III ,8c In III ,8c Fe(II/III),8d8h Cu(I/II),8h,8i,10 Zn II ,8b,8j,8k Mn II ,8k,8l Ag I[9i,11] ] and Ln III[8b,9] (Ln = La, Eu, Ce, Tb, Lu) also play a very important role in the formation of triple‐stranded helicates. The metallo centers in the helicates impart a cationic charge, which is expected to enhance the potential use of such triple‐stranded helicates in chemical and biochemical domains, particularly, in DNA labeling and recognition 8d,9d.…”
Section: Introductionmentioning
confidence: 99%